Evaluation of improvement plans in inclusion-oriented schools - Arnaiz Sánchez, Pilar; Azorín Abellán, Cecilia Mª; García Sanz, Mari Paz (Profesorado, Revista de Currículum y Formación del Profesorado, 2015)
The aim of this article is to assess the planning, implementation and evaluation of plans for improving diversity awareness from the perspective of teachers working in schools with an inclusive approach. To this end, case studies are presented involving five state schools in the Region of Murcia covering Nursery, Primary and Secondary School levels. The studies were conducted in collaboration with university research staff responsible for the project. The results derived from an ad hoc questionnaire indicate that the teachers appreciated the process followed during the planning and implementation of the improvement plans. However, with regard to the evaluation phase, difficulties were perceived in adapting the instruments used. It also makes clear the need for closer collaboration for a more truly effective university-school relationship.